Womanist Poetics: Emily Dickinson, Gertrude Stein, and Audre Lorde - Telmissany, Aya (AUC Knowledge Fountain, 2022)
Today, the sentimentality associated with poetry is often condescendingly dubbed in a patriarchal society as “feminine poetry.” The first women poets who dared to attempt the pen were often met with attacks on their femaleness and harsh critiques of their writing which was likened to sorcery and witchcraft. Emily Dickinson, Gertrude Stein, and Audre Lorde are three American women poets who countered these attacks and turned them inside out in favor of their own womanist poetics. They wrote about experiencing the world as women and most importantly about experiencing poetry as women. What happens to poetry when a woman appropriates it as a craft? Is it altered in any fundamental way? Does it remain the same? Is it in a way recreated as a new and distinct genre? How does gender impact the poetry and poetics of Dickinson, Stein, and Lorde? and to what extent do their contributions appropriate and reshape patriarchal poetry? These are all questions which this project attempts to answer through an analysis of poetry extracted from works by these three women poets: Dickinson’s The Collected Poems of Emily Dickinson (1955), Stein’s Tender Buttons (1914) and Stein: Writings 1903-1932 (1998), and Lorde’s The Collected Poems of Audre Lorde (2000). Poems are closely read and analyzed through Gilbert and Gubar’s methodology of sexual linguistics which uses aspects of the anatomy of the female body to reclaim the poetic craft for themselves and to challenge the existing sexist and patriarchal models on which the history of poetry and authorship is constructed.